A Role for Fc Function in Therapeutic Monoclonal Antibody-Mediated Protection against Ebola Virus - Gunn, Bronwyn M.; Yu, Wen-Han; Karim, Marcus M.; Brannan, Jennifer M.; Herbert, Andrew S.; Wec, Anna Z.; Halfmann, Peter J.; Fusco, Marnie L.; Schendel, Sharon L.; Gangavarapu, Karthik; Krause, Tyler; Qiu, Xiangguo; et al. (Cell host & microbe, 2018)
The recent Ebola virus (EBOV) epidemic highlighted the need for effective vaccines and therapeutics to limit and prevent outbreaks. Host antibodies against EBOV are critical for controlling disease, and recombinant monoclonal antibodies (mAbs) can protect from infection. However, antibodies mediate an array of antiviral functions including neutralization as well as engagement of Fc-domain receptors on immune cells, resulting in phagocytosis or NK cell-mediated killing of infected cells. Thus, to understand the antibody features mediating EBOV protection, we examined specific Fc features associated with protection using a library of EBOV-specific mAbs. Neutralization was strongly associated with therapeutic protection against EBOV. However, several neutralizing mAbs failed to protect, while several non-neutralizing or weakly neutralizing mAbs could protect. Antibody-mediated effector functions, including phagocytosis and NK cell activation, were associated with protection, particularly for antibodies with moderate neutralizing activity. This framework identifies functional correlates that can inform therapeutic and vaccine design strategies against EBOV and other pathogens. [Display omitted] •Fc-effector profiles of 168 Ebola virus-specific monoclonal antibodies were defined•Effector function correlated with protection for partially neutralizing antibodies•Non-protective, strongly neutralizing antibodies fail to induce phagocytosis•Profiles of protective antibodies may aid in design of future immunotherapeutics While antibodies provide protection against Ebola virus, the mechanism is unclear. Gunn et al. dissect the contribution of Fc-functions to protection using a library of Ebola virus-specific antibodies. Fc function was a critical predictor of protection across neutralizing and non-neutralizing antibodies, pointing to synergy between Fc- and Fab-mediated antibody-functions against Ebola.